Gambaran Karakteristik dan Angka Kejadian Postpartum Blues pada Ibu Postpartum di Wilayah Puskesmas Jatinangor - Kusumah, Lidya Nazhifa; Hermayanti, Yanti; Setyorini, Dyah (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Postpartum blues occurs in 1 up to 2 out of 1.000 mothers in Indonesia. The mothers with postpartum blues can give a bad impact for both mothers and babies. Nurses play an important role in intend to prevent the worst impact can possibly happen caused by postpartum blues by identifying the risk factors and do assessment as an early detection of the symptoms in the mothers after childbirth.  Early detection was conducted to figure out the development of mothers’s psychological adaptation and also to detect any psychological disorders that occurred to the postpartum mothers. The purpose of this study was to identify the characteristics and the incidence of postpartum blues in Jatinangor Health Care Service Area. A descriptive study design using a quantitative approach was used for this study by reviewing the characteristics of the postpartum mother and identify the incidence of postpartum blues. The population of this study was a postpartum mother who gave birth in Jatinangor Health Care Service and midwife practice in Jatinangor Health Care Service work area in February 2024 with the nonprobability sampling technique that applied purposive samplings methods and obtained 38 respondents. This study used primary data, collected with the standardized instrument, Edinburgh Postnatal Depression Scale (EPDS) questionnaire. Data analysed by used univariate analysis of frequency distribution. The findings of the research showed that the incidence of postpartum blues occurred in 21 respondents (55%). With the characteristics of the vast majority of respondents are aged 20-30 years (81.6%), are multipara mothers (78.9%), are household mothers (86.8%), have a high middle school education (50%), have a very high income (>3.5k) (31.6%), have a spontaneous birth (86.8%), are a planned pregnancy (86.8) and have good social support (89.5%). As from the result of this study, it can be concluded that in Jatinangor Health Care Service Area there is a high incidence of postpartum blues in postpartum mothers before discharge, with an incidence rate of 21 respondents (55%). Accordingly, it is hoped that the incidence rate of postpartum blues in Jatinangor Health Care Service Area is expected to decrease by improving a program of maternal psychological health education from pre-pregnancy, pregnancy and postpartum in order to increase maternal knowledge about the risk factors and symptoms of postpartum blues. Keywords: EPDS, Postpartum, Postpartum Blues ABSTRAK Postpartum blues terjadi pada 1 hingga 2 dari 1000 ibu di Indonesia. Kondisi ibu dengan postpartum blues dapat menimbulkan dampak yang buruk bagi ibu dan bayi. Perawat memiliki peranan penting dalam upaya pencegahan terjadinya dampak terburuk akibat postpartum blues dengan upaya mengidentifikasi faktor risiko dan deteksi dini gejala postpartum blues pada ibu setelah melahirkan. Deteksi dini dilakukan untuk mengetahui perkembangan adaptasi psikologis ibu postpartum serta mendeteksi gejala postpartum blues. Tujuan dari penelitian ini adalah untuk mendapatkan gambaran karakteristik dan angka kejadian postpartum blues di wilayah Puskesmas Jatinangor. Penelitian ini menggunakan metode deskriptif kuantitatif dengan melihat gambaran karakteristik ibu postpartum dan angka kejadian postpartum blues. Populasi penelitian merupakan ibu postpartum yang melahirkan di Puskemas Jatinangor dan praktik bidan di wilayah kerja Puskesmas Jatinangor pada bulan Februari 2024 menggunakan teknik sampling nonprobability sampling dengan metode purposive sampling. Jumlah sampel sebanyak 38 responden. Penelitian ini menggunakan data primer dengan pengumpulan data menggunakan kuesioner baku Edinburgh Postnatal Depression Scale (EPDS). Data dianalisis secara univariat disajikan dalam distribusi frekuensi. Hasil penelitian menunjukan bahwa kejadian postpartum blues terjadi pada 21 responden (55%). Dengan karakteristik mayoritas responden berusia 20-30 tahun (81.6%), merupakan ibu multipara (78.9%), menjadi ibu rumah tangga (86.8%), berpendidikan SMA (50%), memiliki pendapatan sangat tinggi (>3.5jt) (31.6%), mengalami persalinan spontan (86.8%), merupakan kehamilan yang direncanakan (86.8%) dan memiliki dukungan sosial yang baik (89.5%). Dari hasil penelitian ini, dapat disimpulkan bahwa di wilayah Puskesmas Jatinangor terjadi angka kejadian postpartum blues yang tinggi pada ibu postpartum sebelum dipulangkan, dengan angka kejadian mencapai 21 responden (55%). Maka dari itu diharapkan angka kejadian postpartum blues di wilayah Puskesmas Jatinangor dapat menurun dengan upaya mengembangkan program penyuluhan kesehatan psikologis ibu dari semenjak sebelum kehamilan, masa kehamilan dan setelah persalinan yang bertujuan untuk memberikan pengetahuan pada ibu tentang faktor risiko dan gejala postpartum blues. Kata Kunci: EPDS, Postpartum, Postpartum Blues